Respuesta :
True statements:
a) x + y = y + x ⇒ commutative property of addition
b) (x * y) * z = x * (y * z) ⇒ associative property of multiplication
d) (x + y) + z = x + (y + z) ⇒ associative property of addition
False statements:
c) x - y = y - x should be: x - y = - y + x
e) (x - y) - z = x - (y - z) should be: (x - y) - z = x - (y + z)
a) x + y = y + x ⇒ commutative property of addition
b) (x * y) * z = x * (y * z) ⇒ associative property of multiplication
d) (x + y) + z = x + (y + z) ⇒ associative property of addition
False statements:
c) x - y = y - x should be: x - y = - y + x
e) (x - y) - z = x - (y - z) should be: (x - y) - z = x - (y + z)
Answer:
a x + y = y + x
b ( x * y ) * z = x * (y * z)
d ( x + y ) + z = x + ( y + z )
i just did it
Step-by-step explanation: